(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the evolution of human languages from their biological and cognitive origins to the complex global linguistic systems of today. By analyzing the interplay between anatomical, social, and technological factors, the study outlines the major stages of linguistic development—ranging from proto-communication to the modern digital era. The paper further highlights how language not only reflects human cognition but also actively shapes it. Within this context, the author introduces the Odam Tili (Human Language) theoretical perspective, emphasizing the phonosemantic and empirical foundations of speech evolution.